Management of Acute Sinusitis; Don’t Forget Orbital Involvement (Medical Forum Monthly, 2024)
Objective: To study the results of management of acute sinusitis and early detection and prevention of devastating orbital complications.Study Design: Experimental studyPlace and Duration of Study: This study was conducted at the Lahore General Hospital Lahore and Red Crescent Medical & Dental College Dina Nath, Kasur in the Departments of ENT and Eye from May 2016-May 2019.Materials and Methods: Study included 50 cases presented with symptoms and signs of acute sinusitis as well as symptoms and signs of orbital complications or threatened orbital complications of acute sinusitis. The cases who presented with acute sinusitis were treated by antibiotics, analgesics, local nasal decongestant and systemic nasal decongestants after taking proper history and ENT examination, blood C/E, ESR, nasal swab for C/S and x-ray PNS occipitofrontal and occipitomental views. Those presenting with acute sinusitis along with symptoms and signs of threatened orbital complication were examined by Opthalmic Surgeon and CT Scan of nose and PNS were requested to type the orbital complications of acute sinusitis according to Chandlers classification. The patients aged 18-60 years were included in the study.Results: Among 50 patients, 76.0% were males and 24.0% were female patients. They were diagnosed as having acute sinusitis clinically. Among them, 92% were treated on conventional lines.There were 8% patients suspected of threatened orbital complications as they developed odema of eyelids. Opthalmic consultation and CT Scan showed that they had type-I orbital complication according to Chandlers classification for orbital complications.They were given i/v Augmentin along with Metronidazole infusion along with the other treatment modalities given in acute sinusitis generally.Early diagnosis and aggressive medical management resulted in their recovery.Conclusion: Acute sinusitis with orbital complications are threat to patient vision and life but are uncommon. Opthalmic consultation and urgent CT scan are mandatory if suspicion of orbital complication is arising. CT scan of nose, paranasal sinuses and orbit give guidance for surgical intervention or medical management. If acute sinusitis is diagnosed early and treated promptly and adequately, orbital complication are unlikely and orbital complications even if threatening are picked early. In collaboration with ophthalmic surgeon along with CT scan, they will also not progress to opthalmoplegia, blindness and cavernous sinus thrombosis if treated aggressively.